THE ROLE OF COUNSELING GUIDANCE TO INCREASE STUDENTS’ MOTIVATION AND LEARNING ACTIVITIES AT GRADE VI OF SDN 091263 - Andreas Manurung; Fransius Jonathan Sitepu; Roy Magelhaens Purba; Peniel Marasi Hutahaean; Herman Herman; Muktar Bahruddin Panjaitan (Sean Institute, 2023)
This study aims to evaluate the role of guidance counselors in improving students' academic performance. Descriptive qualitative method was implemented in conducting this research. The data used in this research were students at grade VI of SDN 091263. In addition, the research results also show that students' motivation to learn increases after orientation is carried out. From the results of the study showed that changes and improvements in students. Based on the research, it is known that there is a change in students' interest in learning along with changes in behavior experienced by students. Good analysis results from the research topic to the level of student change. It can be concluded that counseling plays an important role in enhancing students' learning activities and motivation. Therefore, in the learning process, expect the teacher to guide fully and appropriately for students.